Schoolchildren's Lifestyle and Behaviors Relating to Obesity: Collaborative Study in Urban Uganda - Ai Ogata; Fred Wambuzi; Brenda D. Nakirya; Alex Onzima (Evidence-Based Nursing Research)
Context: Child obesity, one of the major contributors to noncommunicable diseases in developing countries, is rising following drastic economic growth and lifestyle changes. In Uganda, noncommunicable diseases as a cause of death have increased from 15% in 1990 to 35% in 2019.